Värinä Tilassa ja Ajassa : Kuopiolaista nykytaidetta. (Kuopio : Kuopio Art Museum, 1992)
Airaksinen, Jouni ; Holm, Pirkko ; Juutilainen, Kari ; Kivinen, Miko & Metsäpelto, Tatu ; Kolehmainen, Markku ; Kolu, Marja ; Laitinen, Ulla ; Meklin, Pentti ; Pohjolainen, Pauno ; Rönkkö, Jaakko ; rönkkö, Riitta ; Soininen, Erkki
Värinä Tilassa ja Ajassa : Kuopiolaista nykytaidetta / Contemporary Art from Kuopio, Kuopio Art Museum, Kuopio, 20.3. - 26.4.1992
boek
Keywords: Kuopio